SITOTOKSISITAS EKSTRAK CAMPURAN BUAH SIRIH, PINANG, DAN KAPUR TERHADAP GALUR SEL 3T3 - Rahmi Amtha; Najla Nadiah; Felix Wong; Ferry Sandra (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
The habit of betel quid chewing has been determined by the WHO as a risk factor for oral cancer due to the carcinogenic substances contained in the mixture. Betel quid chewing is a habit of chewing a mixture of betel, areca nut, and slaked lime with or without tobacco. Until now, betel quid chewing is still one of the habit of people in several countries in Southeast Asia, including Indonesia. The culture of betel quid chewing is still high, especially in eastern Indonesia. The composition of quid used may vary in each area. Eastern Indonesia uses more Piper betel inflorescence (betel fruit) than betel leaf. A study on the cytotoxicity of a mixture of betel fruit, areca nut, and lime originating from NTT Kupang, has never been carried out. This study aimed to determine the cytotoxicity of the mixture extracts mentioned above against 3T3 cell lines fibroblast and its Inhibitory Concentration of 50% (IC50). Cytotoxicity test using MTT assay was carried out on fibroblast 3T3 cell lines on betel mixtures with concentrations of 0, 30, 60, and 120 µg/mL at the 24 and 48 hour incubation period. The extract mixture shows the highest toxic concentration of 120 µg/mL with an incubation period of 48 hours. The IC50 of the extract at the 24 and 48 hour incubation period was 125,21 µg/mL, and 155.06 µg/mL respectively. The mixture of Piper betel inflorescence, areca nut, and lime extracts is cytotoxic against 3T3 cell lines. Keywords: cytotoxicity; piper betel inflorescence; areca nuts; slaked lime; 3T3 AbstrakKebiasaan menyirih telah ditetapkan oleh WHO sebagai salah satu faktor risiko terjadinya kanker mulut dikarenakan adanya bahan karsinogenik yang terkandung dalam campurannya. Menyirih merupakan suatu kebiasaan mengunyah campuran buah sirih, pinang, dan kapur dengan atau tanpa tembakau. Hingga kini menyirih masih menjadi salah satu kebiasaan masyarakat pada beberapa negara di Asia Tenggara termasuk Indonesia. Budaya mengunyah sirih masih cukup tinggi terutama di Indonesia bagian timur. Campuran sirih yang digunakannya dapat bervariasi. Indonesia timur lebih banyak menggunakan buah sirih dibandingkan daun sirih. Penelitian mengenai sitotoksisitas campuran buah sirih, pinang dan kapur yang berasal dari NTT Kupang, belum pernah dilakukan. Tujuan penelitian ini adalah untuk mengetahui sitotoksisitas campuran ekstrak buah sirih, pinang dan kapur terhadap galur sel fibroblast 3T3 serta Inhibitory Concentration of 50% (IC50). Uji sitotoksitas dengan MTT assay dilakukan pada galur sel fibroblast 3T3 terhadap campuran sirih dengan konsentrasi 0, 30, 60 dan 120 µg/mL pada masa inkubasi 24 dan 48 jam. Campuran ekstrak yang menunjukkan sitotoksik paling tinggi pada konsentrasi 120 µg/mL dalam masa inkubasi 48 jam. IC50 ekstrak pada masa inkubasi 24 dan 48 jam adalah 125,21 µg/mL dan 155,06 µg/mL. Campuran ekstrak buah sirih, pinang dan kapur bersifat sitotoksik terhadap galur sel 3T3.